Perceived Stress of Quarantine and Isolation During COVID-19 Pandemic: A Global Survey - Huy, Nguyen T.; Nguyen Tran, Minh Duc; Mohammed Alhady, Shamael T.; Luu, Mai N.; Hassan, Amr K.; Giang, Tran V.; Truong, Le V.; Ravikulan, Rohanti; Raut, Akshay P.; Dayyab, Farouq M.; Durme, Shyam P.; Trang, Vu T.; et al. (Frontiers in Psychiatry, 2021)
Aims. Understanding of the perceived stress and coping strategies adopted by people is important for contemplating the consequences of a pandemic on mental health of people globally. In this study, we intended to assess the perceived stress status of quarantine/isolation globally during the COVID-19 pandemic. Methods. This is a multicentre, multinational cross-sectional study that recruited isolated/quarantined individuals suspected or confirmed to have COVID-19 to assess the psychological impact of the quarantine experience by answering a survey was distributed online. Results. The study was conducted across 63 participating countries gaining 1871 valid responses. There was a higher proportion of female participants in the post-traumatic stress disorder (PTSD) category compared to low stress category (66.0% Vs. 52.0%) and a higher proportion of individuals whose marital status was single had PTSD (57.1%). Also individual's religion may increase the odds of PTSD as Hindus (OR: 4.40, 95 % CI: 2.41, p<0.001). Conclusions. Many factors can predict stress in pandemics such as COVID-19 including female sex, being single, higher education status, and being of the non-healthcare profession.